READING HELPER : MOBILE AUGMENTED REALITY APPLICATION FOR CHILDREN WITH DYSLEXIA - Ng, Sua Jing (Universiti Malaysia Sarawak (UNIMAS), 2020)
An estimated 15-20% of the world’s population suffers from language-based learning disabilities, a neurological disability that impairs the ability of the people in reading and writing. A mobile Augmented Reality (AR) application that uses interactive characters features for children with dyslexia to improving reading. As a result, traditional way of teaching process may requires a lot of time and human resources. There is need to investigate how interactive character with AR technology can motivate children with dyslexia in reading. Therefore, this study aims to develop AlphaRead, a mobile AR application to increase the reading skills of dyslexics. For this purpose, we have designed an application using 3D model and 3D text features in AR context. Also, the blending feature added in the application. The testing and evaluation was conducted by using System Usability Scale (SUS) questionnaire with a group of dyslexic kids from Dyslexia Association Sarawak and Step by Step Learning Centre at Ipoh, Perak. The result proved that this advanced AR application make the learning process more stimulating and entertaining among children with dyslexia.